Individual Psychological Features and Professional Effectiveness in Bank Employees - A S Kuzhnenkova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article presents the results of the research on a ratio of professional efficiency in the bank employees with different activities (lawyers, economists, cash department workers) and their individual psychological characteristics.